2020
DOI: 10.2196/preprints.23548
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

WeChat as a Platform for Baduanjin Intervention in Patients With Stable Chronic Obstructive Pulmonary Disease in China: Retrospective Randomized Controlled Trial (Preprint)

Abstract: BACKGROUND Pulmonary rehabilitation is a crucial part of the nonpharmacological treatment of stable chronic obstructive pulmonary disease (COPD), but management remains problematic. WeChat could serve as a useful tool in patient management. Baduanjin is a popular exercise in China that is usually applied in pulmonary rehabilitation, which has been confirmed to be effective in improving lung function and life quality. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…In our study, Baduanjin improved FEV1% in participants after 12-week Baduanjin intervention. Similar trends of improvement in FEV1% was also observed in another Retrospective Randomized Controlled Trial [21] involving Baduanjin exercise. Meta-analysis [22] included 14 RCTs showed that Baduanjin was effective in improving FEV 1% (Hedge's g = 0.38, CI 0.21 to 0.56, p < 0.001,I2 = 54.74% ) as compared to usual care.…”
Section: Characteristics Of the Study Populationsupporting
confidence: 83%
“…In our study, Baduanjin improved FEV1% in participants after 12-week Baduanjin intervention. Similar trends of improvement in FEV1% was also observed in another Retrospective Randomized Controlled Trial [21] involving Baduanjin exercise. Meta-analysis [22] included 14 RCTs showed that Baduanjin was effective in improving FEV 1% (Hedge's g = 0.38, CI 0.21 to 0.56, p < 0.001,I2 = 54.74% ) as compared to usual care.…”
Section: Characteristics Of the Study Populationsupporting
confidence: 83%